Implementation of Expectation Value and Variance in Decision-Making with Risk in Economic Learning in High School - Susanto, Adi; Amini, Nurul; Subekti, Retno (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Learning outcomes in economics learning at SMA Phase E that are related to material on production activities are that students understand the economic system as a way of organizing various economic activities to meet the various needs of society. Decision-making is commonly found in production activities, and every decision-making process has risks. To overcome this, the concept of probability is needed. Decision-making needs to be taught to students so that they can understand economic activities, which are always dynamic in nature, and the impact of these economic dynamics. Therefore, in learning economics, especially in material on production activities related to decision-making with risk, teachers can start with the theory of expected value and variance so that production activities do not experience losses and can even increase profits. This research aims to explore the relationship between statistical material and economics learning in high school. The research method used is a literature study method and is descriptive-qualitative in nature. The results show that economics teachers in high schools can teach and implement opportunity theory in economics learning in Phase E high schools to equip students to manage various economic activities, especially production activities.